Developing Intercultural Communicative Competence of Cadets through English Language Teaching (Eurasian Journal of Learning and Academic Teaching, 2026)
This article explores the development of intercultural communicative competence (ICC) among cadets through English language teaching. In the context of globalization and increasing intercultural interaction, the ability to communicate effectively across cultures has become essential for future professionals, especially in the field of law enforcement and security. The study highlights the role of English language instruction in fostering not only linguistic skills but also cultural awareness, tolerance, and communicative flexibility. Various teaching methods, including interactive techniques, authentic materials, and culturally oriented tasks, are discussed as effective tools for enhancing ICC. The article emphasizes that integrating intercultural elements into language teaching contributes to the formation of globally competent and professionally prepared cadets.